Tito, the firefighter - Hoppey, Tim.; Hoffman, Kimberly; Vega, Eida de la. ([McHenry, IL] : Raven Tree Press, 2006)
Tito, who admires his neighborhood bomberos (firefighters) and dreams of becoming a one himself, is happy that his ability to speak both English and Spanish actually helps the firefighters save the day.
R.L. 2.6.
Ages 4-8.
Keywords: Fire fighters -- Fiction; Fires -- Fiction; Communication -- Fiction; Spanish language -- Fiction